2022
DOI: 10.1155/2022/3145785
|View full text |Cite
|
Sign up to set email alerts
|

Computer Analysis and Automatic Recognition Technology of Music Emotion

Abstract: With the rapid development of the related computer industry, the use of computer-related technologies has become more and more frequent. The music industry is no exception. The research and analysis of music emotions has been a problem since ancient times. Due to the diversification of music emotions, people with different music in the same piece of music will have different feelings. The research topic of this article is to make a comprehensive analysis of the computer’s automatic identification technology, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Xiang proposed using principal component analysis (PCA) and grammar-based model to extract and select the features of texts and then combined it with the learning framework of support vector machine to classify them. They verified and evaluated the models on corpus data sets [ 10 ]. Lin et al put forward a research method of text emotion classification based on semantic understanding.…”
Section: Related Workmentioning
confidence: 99%
“…Xiang proposed using principal component analysis (PCA) and grammar-based model to extract and select the features of texts and then combined it with the learning framework of support vector machine to classify them. They verified and evaluated the models on corpus data sets [ 10 ]. Lin et al put forward a research method of text emotion classification based on semantic understanding.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, research has shown that music can trigger ANS reactions such as vascular constriction, heart rate fluctuations, muscle tension, and changes in skin temperature (SKT), even when subjects report reduced anxiety and increased relaxation [18]. The study revealed distinct associations between emotions and physiological changes; happiness manifested in significant alterations in respiration, sadness correlated with pronounced changes in blood pressure, heart rate, and SKT, while fear exhibited the highest change in blood flow velocity [19].These findings suggest that music doesn't merely convey easily recognizable emotions but actively generates genuine emotions in the listener [20]. However, the extent to which changes in the ANS and distinctions in musical emotions align with those observed in non-musical emotions remains unclear.…”
Section: Introductionmentioning
confidence: 93%
“…Only students with a solid foundation in music can combine their thoughts and emotions to correctly evaluate music theoretically. [2] Therefore, in order to cultivate students' music appreciation ability, teachers need to effectively teach students the basic knowledge of music and help them continuously improve their appreciation ability.…”
Section: Exploration Of Cultivating Students' Appreciation Abilities ...mentioning
confidence: 99%